Analisis Perbedaan Abnormal Return, Volume Perdagangan Saham Sebelum dan Sesudah Pengumuman Corporate Image Award - Robert Jao; David Jimmiawan (Bongaya Journal of Research in Accounting (BJRA), 2018)
This research aims to investigate if there was difference in abnormal return and trading volume activity beforeand after the announcement of Corporate Image Award. The market reaction is measured by abnormal returnand trading volume activity. The sampel used in this research are all companies which accept the appreciationof Corporate Image Award that listed in Indonesian Stock Exchange (IDX) in 2015, 2016, and 2017 period. Thisresearch uses event study to show market reactions arount the event period, at five days before and after theannouncement by used a market adjusted model for expected return. The research data that used is secondarydata that consist of daily closing price of shares and daily and daily trading volume activity. The statistic methodused to test the hypotheses was Wilcoxon Signed Test. The results of this research proves that there is nodifference abnormal return and trading volume activity before and after Corporate Image Award announcement.